EXAMINATION OF SITE SELECTION and ANALYSE SUBJECT IN SUSTAINABLE ELEMENTARY SCHOOL BUILDING DESIGN - Kayihan, Kutlu Sevinc; Tonuk, Seda (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2008)
Site selection and analysis are initial steps of sustainable elementary school building design. Selections made at this stage will affect the life cycle and the success of the sustainability as a chain reaction. Site selection and open area planning will support or decrease the buildings total sustainability performance. By selecting the proper site a lot of potential environmental threath factors will be eliminated. With this in mind site selection should be made examined in several different aspects. In the entry section of this work site selection and analysis of sustainable elementary school building design will be studied. Beginning of environmental problems and evolving of ecological common sense resulting in sustainable development and reflections of that to the architecture will be touched. Consepts related to the subject are spesified and discussed in the second section. In the third section fundamental principles of sustainable elementary buildings are defined. Sustainable site selection and analysis are discussed in certain headings in the fourth section. Concluion section containes criteria that directs site selection and analysis.
Keywords: Sustainability; ecology; sustainable architecture; sustainable elementary school buildings; sustainable site selection; Architecture